PENGARUSUTAMAAN GENDER DALAM PENGENTASAN KEMISKINAN (Studi Relasi Kuasa Antara Laki-Laki Dan Perempuan Dalam Pengelolaan Keramba Ikan dan Ternak Itik di Kabupaten Sukamara Kalimantan Tengah) - , Sri Pambudi, Ratnawati, SU. MA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Gender mainstreaming that is intended to create gender equality and justice will relate to activities on women empowerment. In the gender mainstreaming, access, participation, control and benefit aspects are made equally between men and women. Fender mainstreaming should also be applied in order to reduce poverty, such as in fish raising basket and duck farm. Poverty reduction that involves men and women will not be separated from power relation in a family. The objective of this research is to identify the extent of power relation in fish raising basket and duck farm management in poverty reduction. The power relation will be seen in access, participation, control and benefit aspects. Based on the observation, participation and power men and women have can be seen. Result of the research indicate that women and men are not limited in getting information access or access for economic resources, which in this case is government aid. Men are more dominant than women in participation in managing aid. Meanwhile, women control over management activity and aid distribution do not appear. Benefit is aspect that women get most, because use of aid management yield is managed by women. Although women get fewer roles in aid management, it does not create jealousness among women. Men seem more dominant in managing aid. Although women also involve in the poverty reduction activity, the involvement is used by men to reveal their domination. The domination appear in access and participation aspects, while in control and benefit aspects manipulation is used in the domination, so the women are not conscious that they are under men power.